Biographical Romance, or The Wonders of ihe Life of An Émigrée of Choice: Fryderyk Járosy (1889–1960) – the Author of Unwritten Memoirs of Life Among the Polish Diaspora in London - Mieszkowska , Anna (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2024)
English version. Original issue: “Archiwum Emigracji” 2009, no. 1 (10) https://apcz.umk.pl/AE/article/view/AE.2009.010